2022
DOI: 10.3389/fphar.2022.924826
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates ferroptosis after subarachnoid hemorrhage via Nrf2/HO-1 signaling pathway

Abstract: Subarachnoid hemorrhage (SAH) is a severe type of stroke featuring exceptionally high rate of morbidity and mortality due to the lack of effective management. Ferroptosis can be defined as a novel iron-dependent programmed cell death in contrast to classical apoptosis and necrosis. Astragaloside IV (AS-IV) is an active ingredient extracted from Astragalus membranaceus with established therapeutic effect on CNS diseases. However, the exact role of ferroptosis in Astragaloside IV-mediated neuroprotection after S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…HO-1 decomposes heme directly, alleviating the damage caused by hemoglobin effectively, and prolonging neuronal protection. Previous studies have also shown that overexpression of HO-1 in cerebral cortex can remarkably reduce delayed cerebral vasospasm and improve the behavioral performance of SAH rats [43][44]. Secondly, heme decomposition products CO and biliverdin are powerful substances for anti-oxidative stress and anti-in ammation.…”
Section: Discussionmentioning
confidence: 97%
“…HO-1 decomposes heme directly, alleviating the damage caused by hemoglobin effectively, and prolonging neuronal protection. Previous studies have also shown that overexpression of HO-1 in cerebral cortex can remarkably reduce delayed cerebral vasospasm and improve the behavioral performance of SAH rats [43][44]. Secondly, heme decomposition products CO and biliverdin are powerful substances for anti-oxidative stress and anti-in ammation.…”
Section: Discussionmentioning
confidence: 97%
“…Most drug-related studies also focus on the up-regulation of GPX4 and whether it can be achieved as a criterion for determining whether a drug is effective for ferroptosis treatment ( Huang et al, 2022 ; Yuan B. et al, 2022 ). SLC7A11, as the critical target regulating GSH synthesis, was also found to be impaired in SAH models ( Liu et al, 2022 ). But in terms of protein expression, the reduction is not as significant as GPX4.…”
Section: The Research Status In Ferroptosis In Hemorrhagic Strokementioning
confidence: 99%
“…Ferroptosis is implicated in many neurological disorders such as traumatic brain injury (TBI) and in chronic neurodegenerative diseases including Alzheimer's disease and Parkinson's disease. 54 , 55 In the field of ischemic stroke, ferroptosis is more extensively studied in hemorrhagic stroke 56 , 57 , 58 , 59 as heme and iron are blood components. Indeed, ferroptosis was observed in neonatal rat hypoxic–ischemic brain injury models.…”
Section: Cell‐specific Role Of Nrf2 In the Acute Phasementioning
confidence: 99%